Elsbeth. Season one [videorecording (DVD)] - King, Robert (Screenwriter); King, Michelle (Television producer) (Paramount, 2024)
Elsbeth Tascioni, an astute but unconventional attorney who utilizes her singular point of view to make unique observations and corner brilliant criminals alongside the NYPD. After leaving her successful legal career in Chicago to tackle a new investigative role in New York City, Elsbeth finds herself jockeying with the toast of the NYPD, Captain C.W. Wagner.